Electronic properties of amorphous silicon carbon are correlated with the methane flow rate - Prayogi, Soni; Cahyono, Yoyok; Darminto, Darminto (Institute of Advanced Engineering and Science, 2025)
This study examines how methane flow rate during the plasma-enhanced chemical vapor deposition (PECVD) process affects the electronic properties of amorphous silicon-carbon (a-SiC) thin films. The films were deposited with varying methane flow rates, and their structural and electronic properties were analyzed using spectroscopic ellipsometry and atomic force microscopy (AFM). Results show that the methane flow rate influences the ratio of sp2 to sp3 carbon bonding, which impacts the material's electronic band structure. Higher methane flow rates increase sp2 carbon content, reducing the bandgap energy and enhancing electrical conductivity. In contrast, lower flow rates lead to higher sp3 bonding, wider band gaps, and decreased conductivity. This study highlights the potential for optimizing methane flow rates in PECVD to tailor the electronic properties of a-SiC films for specific applications. The findings offer valuable insights for designing and optimizing a-SiC materials for electronic devices. Future research will investigate how other deposition parameters and post-deposition treatments affect a-SiC's electronic properties, aiming to further improve material performance for advanced technological applications.